Comparison of the Electrocatalytic Performance of Pt and Pt-Ru for Oxidation of Methanol - Li, Qiuhong (Asian Journal of Chemistry, 2010)
The electrocatalytic properties of platinum and platinum-ruthenium particles incorporated into polyaniline films are investigated for oxidation of methanol in sulphuric acid. It is observed that the electrocatalytic activity of the metal-modified polyaniline electrode depends greatly on the deposition condition of metal particles which can be optimized by the electrochemical formation conditions.